Retrospective comparison of side effects and outcomes of three-dimensional conformal vs. intensity-modulated radiation therapy in the palliative-intent treatment (4 Gy × 5 daily fractions) of canine intranasal tumors (2010–2017) - Fu, Dah-Renn; Weng, Hsin-Yi; Mendez Valenzuela, Carlos Roberto; Vanhaezebrouck, Isabelle F.; Plantenga, Jeannie M. (Frontiers in Veterinary Science, 2023)
Objective: To compare the occurrence of radiation side effects and treatment outcomes in dogs with intranasal tumors treated with a total dose of 20 Gy delivered in 5 daily 4 Gy fractions using computer-based 3D conformal (3DCRT) or intensity-modulated (IMRT) radiation therapy plans. Design: Retrospective case series. Materials and Methods: Medical records for dogs with intranasal tumors treated with 4 Gy x 5 fractions between 2010 and 2017 were reviewed. Radiation side effects, time to local progression (TTLP), progression-free survival (PFS) and survival time (OS) were evaluated. Results: Thirty-six dogs (24 carcinomas, 10 sarcomas and 2 others) met the inclusion criteria. Sixteen were treated with 3DCRT and 20 with IMRT. Clinical signs improvement or resolution were reported in 84% of dogs. The median time to clinical signs improvement was 12 days (1 to 88 days) after the end of treatment. Eight dogs treated with 3DCRT (8/16, 50%) and 5 with IMRT (5/20, 25%) were documented acute radiation side effects. Almost all were classified as grade 1 skin, oral or ocular acute side effects. Only one dog (3DCRT group) demonstrated grade 2 skin side effects. The median TTLP for dogs treated with 3DCRT or IMRT was 238 days and 179 days, respectively (p = 0.967). The median PFS for 3DCRT or IMRT was 228 days and 175 days, respectively (p = 0.940). The median OS for 3DCRT or IMRT was 295 days and 312 days, respectively (p = 0.787). No significantly differences were observed in side effects, TTLP, PFS and OS between 3DCRT and IMRT groups. Conclusions: Palliative-intent conformal radiation therapy given in five daily 4 Gy fractions relieved clinical signs with minimal radiation side effects, with no statistical difference in occurrence between 3DCRT and IMRT dogs.